Is Majelis Ulama Indonesia Same with Darul Ifta Egypt? A Comparative Studies - Abdullah, Umar; Al-Fatih, Sholahuddin (Audito Comparative Law Journal (ACLJ), 2025)
This article aimed to discuss the similarities and differences between Majelis Ulama Indonesia (MUI) and Darul Ifta in Egypt (or Darul Ifta Mesir/DIM), especially from a legal perspective. Both institutions were Islamic organization, a place that Ulama from different perspective or mazhab (legal thought) take a part in issuing fatwa for their country. This article employs the normative juridical method with comparative studies. As a result, MUI cannot be converted into Darul Ifta. MUI with Darul Ifta has reached an advanced stage. The number of experts serving on the MUI fatwa committee is similarly limited. For example, until today, the MUI has only issued hundreds of fatwas, although Darul Ifta receives over 3500 - 4000 incoming fatwas per day. Mustafti or correspondents requesting Darul Ifta fatwas are not confined to local locals but also include outsiders. Members of the Fatwa Commission are indirectly, personally, and scientifically accountable for providing one-by-one responses to the fatwa requested by the correspondent after consulting Islamic legal sources and researching the social context in which the fatwa takes place.